Mechanisms of Familial and UV-induced Melanoma - Jeri D Hughes (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2025)
Melanoma is the most common form of skin cancer in the United States. Melanoma is a disease where cancerous cells derive from melanocytes. Common melanoma susceptibility genes induce dysregulation in the mitogen-activated protein kinase (MAPK) pathway, phosphatase and tensin homolog (PTEN),and AKT expression. Melanoma can be induced through prolonged UV-radiation or familial diagnosis. This article aims to discuss the mechanisms of both familial and UV-induced melanomagenesis
Keywords: Dermatology; Melanoma; UV-radiation; Familial melanoma; Molecular Biology; Susceptibility genes